Clinical and radiological study of single-level degenerative lumbar disc disease in Eastern India Medical College - Krishnendu Sardar; Md Salim Uz Zaman; Soumedhik Dey; Sumana Baidya (Asian Journal of Medical Sciences, 2025)
Background: Low back pain secondary to lumbar disc degenerative disease (LDDD) usually affects young to middle-aged persons. It presents as a sharp shooting type of pain, mild tingling sensation, and a dull ache. There are many risk factors associated with the LDDD, such as advancing age, smoking, and obesity. The annual incidence of prolapsed lumbar intervertebral disc is about 5–10%. Lumbar disc herniation is the pathological condition for which spinal surgery is most often performed. Treatment for lumbar disc herniation can be conservative or surgical, and which one is effective is always controversial. The purpose of conducting this study is to assess different clinical features, magnetic resonance imaging (MRI) characteristics, and postsurgical outcome of single-level lumbar disc disease. Aims and Objectives: To evaluate the clinical symptoms, functional status, and most commonly affected lumbar level in patients with single-level LDDD along with post-operative outcome of that level. Materials and Methods: 50 symptomatic patients who were diagnosed as single-level disc degenerative disease by MRI, not responding to conservative treatment, were included in our study. It is conducted over a period of 2 years in Bangur Institute of Neuroscience. Any patient having previous surgery is excluded from our study. Results: It has been found that L4-L5 level disc herniation and posterolateral site is more common. The most common type is protrusion. Conclusion: It helps surgeons to locate the level, type, and site of degenerative disc disease in symptomatic patients who fail to respond to conservative management. Surgical outcome is better than conservative management.